Pediatric Non-Alcoholic Fatty Liver Disease - Haley Bush; Pegah Golabi; Zobair M. Younossi (MDPI AG, 2017)
Abstract: With the increase in the prevalence of obesity, non-alcoholic fatty liver disease (NAFLD) has become among the leading causes of chronic liver disease in the pediatric age group. Once believed to be a "two-hit process", it is now clear that the actual pathophysiology of NAFLD is complex and involves multiple pathways. Moreover, NAFLD is not always benign, and patients with non-alcoholic steatohepatitis (NASH) are at increased risk of developing advanced stages of liver disease. It has also been shown that NAFLD is not only a liver disease, but is also associated with multiple extrahepatic manifestations, including cardiovascular diseases, type 2 diabetes, and low bone mineral density. Although the data is scarce in the pediatric population, some studies have suggested that long-term mortality and the requirement of liver transplantation will continue to increase in patients with NAFLD. More studies are needed to better understand the natural history of NAFLD, especially in the pediatric age group.